Cultural internationalism : the logic of a new international governance - Guo, Shuyong, 1968-; Zhang, Xiaoyin (London ; New York : Routledge, Taylor & Francis Group, 2021)
"By studying the significance and mechanisms of cultural internationalism, this book aims to help emerging international powers constructively engage in global governance in a multipolar world, with particular regard to cultural considerations. Global governance has, to a degree, become more significant than traditional power politics on the international stage. Against this backdrop, the author proposes the idea of a cultural internationalism that centres upon cultural interactions, dialogues and mutual learning and calls for international cooperation and a reconstruction of the world order. The rise of the G20 and the BRICS countries are cited as an example of the efficacy of international coordination communities built upon both cultural consensus and shared economic foundations, as well as international interactions. The author also explores China's case to explore practical approaches to the fostering of supranational responsibilities while not neglecting national interest. The book will appeal to academics and general readers interested in international relations, globalization and Chinese diplomacy"--
Prologue. From 'major changes unprecedented' to 'the governance logic of international politics' -- Concepts and classifications of national governance and international governance -- Cultural dimension of international governance -- Related theories of international governance and China's choice -- New developments in global governance and China's mindset in the period of historic opportunity -- The divided international society and China's role in global governance -- Understanding the new type of international governance : a case study of the BRICS countries -- Meta-internationalism : the new type of international governance requires neointernationalism -- Culture and national interests under the new trend of global governance -- New cultural internationalism facing contemporary cultural crises -- Opportunities and challenges for China's cultural internationalism -- Postscript. The theoretical boundaries, practical conditions, and policy significance of cultural internationalism.
OCLC-licensed vendor bibliographic record.
Keywords: BRICS; Internationalism; International relations and culture; Cultural relations; China -- Foreign relations -- Case studies; POLITICAL SCIENCE / General; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / International Relations / Diplomacy